(untitled) (Global Journal of Human-Social Science, 2017)
This paper examines the association between a variety of health indicators and GDP growth rates over the period 1972-2011 using a balanced panel dataset consisting of seven members of the South Asian Association for Regional Cooperation SAARC excluding Afghanistan We explicitly accounted for interactions between survival rates and lagged GDP levels as well as endogeneity issues The findings revealed that the survival rate and other health indicators are positively associated with GDP growth Accordingly investments that promote improvements in health outcomes in South Asian countries could potentially accelerate economic development in the region